Effect of exercise‐induced bronchoconstriction on the configuration of the maximal expiratory flow‐volume curve in adults with asthma - Klimenko, Oksana; Luu, Peter; Dominelli, Paolo; Noggle, Nathan; Petrics, Gregory; Haverkamp, Hans Christian (Physiological reports, 2023)
We determined the effect of exercise‐induced bronchoconstriction (EIB) on the shape of the maximal expiratory flow‐volume (MEFV) curve in asthmatic adults. The slope‐ratio index (SR) was used to quantitate the shape of the MEFV curve. We hypothesized that EIB would be accompanied by increases in SR and thus increased curvilinearity of the MEFV curve. Adult asthmatic ( n  = 10) and non‐asthmatic control subjects ( n  = 9) cycled for 6–8 min at 85% of peak power. Following exercise, subjects remained on the ergometer and performed a maximal forced exhalation every 2 min for a total 20 min. In each MEFV curve, the slope‐ratio index (SR) was calculated in 1% volume increments beginning at peak expiratory flow (PEF) and ending at 20% of forced vital capacity (FVC). Baseline spirometry was lower in asthmatics compared to control subjects (FEV1% predicted, 89.1 ± 14.3 vs. 96.5 ± 12.2% [SD] in asthma vs. control; p  < 0.05). In asthmatic subjects, post‐exercise FEV1 decreased by 29.9 ± 13.2% from baseline (3.48 ± 0.74 and 2.24 ± 0.59 [SD] L for baseline and post‐exercise nadir; p  < 0.001). At baseline and at all timepoints after exercise, average SR between 80 and 20% of FVC was larger in asthmatic than control subjects (1.48 ± 0.02 vs. 1.23 ± 0.02 [SD] for asthma vs. control; p < 0.005). This averaged SR did not change after exercise in either subject group. In contrast, post‐exercise SR between PEF and 75% of FVC was increased from baseline in subjects with asthma, suggesting that airway caliber heterogeneity increases with EIB. These findings suggest that the SR‐index might provide useful information on the physiology of acute airway narrowing that complements traditional spirometric measures. We applied the slope‐ratio (SR) analysis to determine the effect of exercise‐induced bronchoconstriction (EIB) on the shape of the maximal expiratory flow‐volume curve in asthmatic adults. Post‐exercise SR between peak expiratory flow and 75% of vital capacity was increased from baseline in subjects with asthma, suggesting that airway caliber heterogeneity increases with EIB.